With teeth - Arnett, Kristen (Riverhead Books, 2021)
"From the author of the New York Times-bestselling sensation Mostly Dead Things: a surprising and moving story of two mothers, one difficult son, and the limitations of marriage, parenthood, and love. If she's being honest, Sammie Lucas is scared of her son. Working from home in the close quarters of their Florida house, she lives with one wary eye peeled on Samson, a sullen, unknowable boy who resists her every attempt to bond with him. Uncertain in her own feelings about motherhood, she tries her best--driving, cleaning, cooking, prodding him to finish projects for school--while growing increasingly resentful of Monika, her confident but absent wife. As Samson grows from feral toddler to surly teenager, Sammie's life begins to deteriorate into a mess of unruly behavior, and her struggle to create a picture-perfect queer family unravels. When her son's hostility finally spills over into physical aggression, Sammie must confront her role in the mess--and the possibility that it will never be clean again. Blending the warmth and wit of Arnett's breakout hit, Mostly Dead Things, with a candid take on queer family dynamics, With Teeth is a thought-provoking portrait of the delicate fabric of family--and the many ways it can be torn apart"--